Achieving socially significant reductions in problem behavior following the interview‐informed synthesized contingency analysis: A summary of 25 outpatient applications. Issue 1 (10th January 2018) - Jessel, Joshua; Ingvarsson, Einar T.; Metras, Rachel; Kirk, Hillary; Whipple, Ruth
Abstract : Jessel, Hanley, and Ghaemmaghami (2016) reported the results of 30 interview‐informed, synthesized contingency analyses (IISCAs) and found the IISCAs to be an effective tool for identifying the functions of problem behavior across a variety of topographies, participants, and settings. Jessel et al. did not, however, include data on the effectiveness of the corresponding treatments. In the current study, we collected and summarized 25 additional applications, from analysis to treatment, in which the IISCA was applied in an outpatient clinic. The IISCA identified various social functions of problem behavior, which informed personalized treatments of functional communication training with contingency‐based reinforcement thinning. A 90% or greater reduction in problem behavior was obtained for every participant by the end of the treatment evaluation. The assessment and treatment process was socially validated by caregivers who rated the procedures highly acceptable and helpful, and the improvement in their child's behavior highly satisfactory.